Modernization Of Islamic Education From Ahmad Dahlan's Perspective and Its Relevance In The Digital Era - Luklu'ul Islamiyati; Sakti Cahyo Nugroho; Mahmud Adam; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the concept of the modernization of Islamic education from Ahmad Dahlan’s perspective and examine its relevance in addressing the challenges of the digital era. The study employs a qualitative approach using a library research design. Data were collected from primary sources, including Ahmad Dahlan’s writings, ideas, and documents on Islamic educational reform and the Muhammadiyah movement, as well as secondary sources such as scientific journals, books, research articles, conference proceedings, and previous studies related to Islamic education, digital transformation, and character education. Data collection was conducted through documentation techniques, while data analysis utilized content analysis involving data reduction, theme classification, interpretation, and conclusion drawing. The findings reveal that Ahmad Dahlan’s modernization of Islamic education is rooted in the spirit of tajdid (Islamic reform), emphasizing the integration of religious and general sciences, character formation, social awareness, contextual learning, and openness to scientific and technological advancement. Therefore, Ahmad Dahlan’s concept of educational modernization offers a balanced framework for developing adaptive, progressive, and value-based Islamic education capable of responding to contemporary challenges without losing its spiritual identity.